The Digital Museum: A Case Study of Digital Applications at the National Palace Museum (Global Journal of Human-Social Science, 2016)
In our current age of information digitization democratization and globalization technology has changed people s habits to expect immediately accessible information Technology is no longer merely a tool but a new medium capable of instantaneously and seamlessly altering people s internal consciousness As the treasure houses of art and artifacts museums have evolved with the times to establish its presence and accessibility in the information age digitizing its collection from which new exhibition formats and museum experiences can be created This paper conducts a literature review of digitization s impact on the curatorial efforts of major world-renowned national museums as the context for a case study evaluating the fruits of digitization at the National Palace Museum in recent years with a focus on the most recent new media art exhibition the Giuseppe Castiglione Lang Shining New Media Art Exhibition
Keywords: new media art; digital art; digital curation; digital archive; national palace museum; database; information society